Mengembalikan Sekolah ke Habitatnya - Nursisto, Nursisto (Magister Administrasi Publik (MAP) FISIPOL Universitas Gadjah Mada, 2001)
School and community based management is a progressive step to empower education system in Indonesia by giving a greater role to society in managing a school. By giving opportunities to the society to participate in education, schools will ger a benefit from any direct contribution, both in the form of ideas and funds. In this kind of education system the government does not have to dominate schools in managing and pursuing their goals. With the application of school and community based management, the schools would be entrusted to manage themselves, to design their programs based on supporting environment and to assure good achievement for the students. Schools management would be transparent for all stakeholders and dynamic cooperation among the stakeholders would be materialised. The basic idea for school and community based management is to return the schools to their habitat.